Análisis de nuevos mercados internacionales para incrementar la rentabilidad de la empresa Infrues S.A. - Infante Suarez, Ruddy Alexandra (2015)
In the present work degree on the theme "Analysis of new international markets to increase profitability INFRUES COMPANY S.A.", the reality of our country internationally in terms of existing markets for banana exports will explore the obstacles, competitors, analysis of the country to which we can include as a possible export market, and most importantly, figures and percentages that will let us know the wide possibility of entering this market. The plan examines the national and international management when exporting, establishing actual results and market indicators, a larger opening for our company to position ourselves in the world and recognized as a company representative dimension to this effect must formulate a viable model technically validated by the board of the company INFRUES S.A., for the integration of programs and services the export plan provides for the company, allowing increasing net income same and the efficiency and effectiveness of all areas of the organization positively impact results being of all that we are part of this company. Identify and learn ways to work collaboratively across programs and areas of the company “INFRUES S.A.”. Keep a single register of specialized export in this country Propose a strategy of continuous improvement, familiarize and sensitize employees in good agricultural practices, and the conceptual framework of the project is based on an export plan, designed in the area of marketing and sales which allow guiding the exploration and investigate the possibility of entering the market International as a solid company in exporting bananas to the first world countries like Italy, to perform the analysis of the situation we examine the main factors determining the business environment and the product and affect the marketing thereof; among the factors leading company INFRUES S.A. We, characteristics of the fruit, market potential, competition, comparison with similar products, technology, regulatory framework and critical success factors for the product. This paper is focused on a number of references based on scientific journals that support the work done. Addition it discloses the description of the proposal in which the structural components are given a short description of the company, the objectives is to be achieved, and information necessary for the inclusion of bananas in a target market of Italy, and the effect the project is analyzed causes in the social, environmental and economic, it is intended that the company has increased profitability with positioning new markets.